An Overlooked Source of Galdós's “Marianela”: “Pepita Jiménez” - Kaplan, Gregory (Tropelías: Review of Literary Theory and Comparative Literature, 2003)
Juan Valera's Pepita Jiménez voices the author's conception of perfect love, according to which physical and spiritual elements are necessary for a harmonious union to exist. As a manifestation of this notion, the male protagonist of Pepita Jiménez experiences an intellectual transformation that causes him to abandon his spiritual vision of his future in favour of a marriage that fulfills his physical and spiritual needs. In Marianela, by Benito Pérez Galdós, the male protagonist undergoes a similar change before rejecting a spiritual commitment and entering into marriage. This parallel suggests that Galdós sought inspiration in Valera's masterpiece and enlists the two works as components of one of the novelistic dialogues in which Galdós frequently engaged.
Keywords: Benito Pérez Galdós; Juan Valera